Longitudinal Changes in Fecal Microbiota During Hospitalization in Horses With Different Types of Colic - Clémence Loublier; Marcio Costa; Bernard Taminiau; Laureline Lecoq; Georges Daube; Hélène Amory; Carla Cesarini (Journal of Veterinary Internal Medicine)
ABSTRACT Background Research on fecal microbiota changes during hospitalization of horses with colic is emerging. Objectives Describe changes of the fecal microbiota during hospitalization of horses with colic caused by inflammatory (INFL), simple (SIMPLE), and strangulated (STR) obstructions, and investigate associations with survival. Animals Twenty‐three horses with colic: 9 in INFL, 5 in STR, and 9 in SIMPLE groups. Seventeen horses survived, and 6 were euthanized. Methods Prospective observational study. Fecal samples were collected on admission (D1), on days 3 (D3) and 5 (D5). Bacterial taxonomy profiling was obtained by V1V3 16S amplicon sequencing. Data were compared using a 2‐way permutational analysis of variance (PERMANOVA). Linear discriminant analysis Effect Size (LEfSE) analysis identified significant bacterial population differences, with significance set at p < 0.05 and a linear discriminant analysis (LDA) cut‐off > 3.0. Results Alpha diversity indices remained stable during hospitalization within each colic group. However, at D5, the INFL group had significantly higher richness (p < 0.01) and diversity (Shannon, p < 0.001 and Simpson, p < 0.05) than other colic types. Beta diversity (Jaccard membership and Bray‐Curtis indices) was significantly different in the INFL compared to SIMPLE and STR groups (both p < 0.001) but not between SIMPLE and STR. Beta diversity membership analysis by analysis of molecular variance (AMOVA) indicated a significant difference between survivors and non‐survivors within the INFL group (p < 0.01). Increased relative abundances of Bacilliculturomica and Saccharofermentans were associated with survival. Conclusions Microbiota showed no significant variation over 5 days of hospitalization. Colic type influenced fecal microbiota more than hospitalization duration. Specific bacterial populations may differ between survival and non‐survival groups.